Reservoir Identification Based on Gravity Method at “AUN” Geothermal Field - Hafidah Annisa Dwi; Daud Yunus; Usman Alfian (E3S Web of Conferences, 2019)
Sumatra Island has the largest geothermal potential in Indonesia spread along the subduction zone between the Indian-Australian plate and the Eurasian plate. “AUN” geothermal field located in Sumatra Island and considered to be one of the largest potential geothermal prospects in Indonesia. This study is focused on identifying the prospect of “AUN” geothermal field using gravity method. First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) analysis were applied in order to determine a more accurate boundary of the fault. 3D inversions of gravity data were used to reconstruct subsurface model. The result show that analysis of First Horizontal Derivative (FHD) and Second Vertical Derivative (SVD) can confirm southwest-northeast fault and caldera structure as a boundary of geothermal reservoir and 3D gravity inversion can show subsurface layers with density 2.5 gr/cc to 2.8 gr/cc inside the boundary which is determined as a heat source in “AUN” geothermal field.